Pengembangan Bahan Ajar Membaca Berbasis Destinasi Wisata Bahari di Kecamatan Kaur pada Pembelajaran Menulis Narasi Kelas IV Siswa Sekolah Dasar - Djuanita, Ana (UNIB Press, 2025)
This study aims to produce teaching materials and analyze the needs of teachers and fourth grade students for narrative writing teaching materials based on marine tourism destinations, produce narrative writing reading materials based on marine tourism destinations for fourth grade elementary school students, test and analyze the feasibility of reading teaching materials writing tourist destination-based narratives for fourth grade elementary school students. The type of research used is research and development research and development (R&D). The research subjects were teachers and fourth grade students of SD Negeri 90 Kaur. The object of the research is the development of reading teaching materials based on marine tourism destinations in Kaur Regency in learning to write narratives for fourth grade elementary school students, using pictures and narrative texts. From the research, it can be concluded that the needs of teachers and students are: (1) Reading Teaching Materials Based on Kaur Marine Tourism Destinations in Writing Narrative Indonesian Language Lessons for Class IV at SDN 90 Kaur, (2) Teaching Materials designed with attractive colors and images, (3 ) Reading Teaching Materials Based on Kaur Marine Tourism Destinations in Writing Narratives that are in accordance with the level of student characteristics and are easy to understand. Reading Teaching Materials made by researchers have been declared eligible by the validation team after the validator validates the Teaching Materials. The response of teachers and students to Reading Teaching Materials Based on Kaur Marine Tourism Destinations in Writing Narratives in Grade IV SDN 90 Kaur is positive, this is evident from the questionnaires given to teachers and students.